Anti-browning effects of citronellal on fresh-cut taro (Colocasia esculenta) slices under cold storage condition - Wang, Bin; Wang, Yukun; Huang, Yongyan; Jiang, Yuanyuan; He, Jinming; Xiao, Yanhui (Frontiers in Sustainable Food Systems, 2022)
The browning on the cut surface is a big problem reducing the quality of fresh-cut taro (FCT), which causes severe postharvest losses and may raise environmental impacts. Citronellal (CA) is a natural compound in several aromatic plants. This study investigated the effects of CA treatments in different concentrations (0.2, 0.5, and 1 mL/L) on the browning of FCT under cold storage at 5°C. The results indicated that low-dose (0.2 mL/L) CA treatment showed best anti-browning effects, reflecting at the maintained L* values but the reduced a*, b* and browning index values by CA treatment during cold storage. A repeated experiment using 0.2 mL/L CA confirmed fine anti-browning effects again. Furthermore, CA (0.2 mL/L) treatment markedly reduced the contents of total phenolic compounds and soluble quinones, restrained the activities of phenylalanine ammonia lyase, peroxidase and polyphenol oxidase, down-regulated the gene expression of 18 browning-related enzymes in FCT. These results together strongly demonstrate the validity of CA on FCT browning prevention. Given that CA is a natural compound existing in plants, low concentration of CA possesses strong anti-browning effects on FCT and also inhibitory effects on pathogens, implying that its application has potentiality to preserve high quality of fresh-cut produce for processing and storage. Moreover, CA treatment significantly decreased malondialdehyde contents and lipoxygenase activity. Correlation analysis indicated that the lipid peroxidation of cell membrane was mostly correlated with FCT browning. The results suggest that membrane lipid peroxidation was a possible reason for FCT browning and CA treatment reduced browning, in part, through alleviating the lipid peroxidation of cell membrane. Overall, our results demonstrate that CA is a novel browning mitigator for FCT under cold storage condition.